Contemporary Shariah Issues Related to Operating Costs of Zakat Distribution by Islamic Financial Institution - Munawwaruzzaman Mahmud; Muhammad Aqil Syafiq Jamaludin (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025